Influence of Family Involvement and Children’s Socioemotional Development on the Learning Outcomes of Chilean Students - Saracostti, Mahia; Lara, Laura; Martella, Diana; Miranda, Horacio; Miranda-Zapata, Edgardo Daniel; Reininger, Tal (Frontiers in Psychology, 2019)
There is an extensive body of evidence to support both family involvement and students’ socioemotional development as key factors in the promotion of learning outcomes. However, there is insufficient evidence to establish exactly what this impact is when both factors are considered simultaneously. Therefore, the aim of this study is to analyze the influence of family involvement and socioemotional development on learning outcomes of Chilean students, identifying the structure that most correctly identifies the influence of the predictor variables (family involvement and socioemotional development) on learning outcomes. We present the following three hypotheses that consider possible basic interrelation structures: (1) The influence of family involvement on learning outcomes is mediated by students’ socioemotional development (mediation hypothesis); (2) The influence of family involvement on learning outcomes is moderated by students’ socioemotional development (moderation hypothesis); (3) Family involvement and students’ socio emotional development directly affect learning outcomes (covariance hypothesis). The structures were evaluated by means of a structural equation model analysis. The study included 768 students who attended second and third elementary grades in Chilean schools. The children were between 7 and 11 years old (M = 8.29, SD = 0.86); 41.3% were girls and 58.7% were boys. The results show that family involvement and students’ emotional development directly affect learning outcomes (CFI = 0.995, TLI = 0.993, RMSEA = 0.016). From the results, we can conclude that the data support the hypothesis that both family involvement and socioemotional development are predictors of learning outcomes, thereby rejecting that the impact of family involvement on learning outcomes is mediated or moderated by socioemotional development.